If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -3x + 2 + -1x = x + x Reorder the terms: 2 + 8x + -3x + -1x = x + x Combine like terms: 8x + -3x = 5x 2 + 5x + -1x = x + x Combine like terms: 5x + -1x = 4x 2 + 4x = x + x Combine like terms: x + x = 2x 2 + 4x = 2x Solving 2 + 4x = 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 2 + 4x + -2x = 2x + -2x Combine like terms: 4x + -2x = 2x 2 + 2x = 2x + -2x Combine like terms: 2x + -2x = 0 2 + 2x = 0 Add '-2' to each side of the equation. 2 + -2 + 2x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + 2x = 0 + -2 2x = 0 + -2 Combine like terms: 0 + -2 = -2 2x = -2 Divide each side by '2'. x = -1 Simplifying x = -1
| 13.4x=2.6x | | .5x=9-.5x | | 7x-19=-23+6x | | 15s^2-24s=63 | | y-5=7x | | 3r-7=-1+r | | 167=6+7(2+7r) | | (2x-3)(3x-4)-(x-13)(x-4)=40 | | y^2-y=28 | | 12=512+4 | | b^2-3b=88 | | x+5(5+2)+x-3(4+9)= | | 11x+35+90=90 | | 2x^2-8x+16=10 | | 11x+35+90=180 | | (5x+4)(x+3)=0 | | .75x+.05(18-x)=.10(-117) | | 49b^2-5=-1 | | (r-2)(r+7)=9 | | -20t+10=6 | | 18h^2+33h=-5 | | 49b^2-5=41 | | 63=2n+9 | | -0.3q=9 | | U=5(9n+30)+9(n+1) | | 2-7(d-1)=3(d-2)-5(f+3) | | d^2-13d+40=0 | | -5a-7=48 | | 1.5x^2-2.5x-1.5=0 | | x-6/x+6=1/5 | | 0=8x^2+750+1600 | | (6x+4)-(2x-5)= |